2008 7th International Pipeline Conference, Volume 3 2008
DOI: 10.1115/ipc2008-64474
|View full text |Cite
|
Sign up to set email alerts
|

Crack Propagation and Arrest in X70 1420x21,6mm Pipes for New Generation of Gas Transportation System

Abstract: The ductile fracture arrest capability of gas pipelines is seen as one of the most important factors in the future acceptance of new high strength pipeline steels for high pressure applications. New North-European pipeline project is based on application of X70 pipes designed for high gas pressure of 9,8MPa. To study fracture propagation behavior in cold climate the full scale tests were carried out using longitudinally and spiral welded pipes with different microstructure of base metal. Results of the tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It's interesting to note the presence of a small volumetric fraction of bainite / degenerated pearlite and the absence of acicular ferrite in X70 steel. For a pipeline steel, if these constituents can be achieved, it will be with better properties combination [24][25][26][27][28][29][30][31][32][33][34] , such as high mechanical strength, excellent fracture toughness, good H 2 S resistance, reduction of the Bauschinger effect and superior fatigue behavior, than the polygonal ferrite -pearlite microstructure. The distribution of inclusions in the two steels was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…It's interesting to note the presence of a small volumetric fraction of bainite / degenerated pearlite and the absence of acicular ferrite in X70 steel. For a pipeline steel, if these constituents can be achieved, it will be with better properties combination [24][25][26][27][28][29][30][31][32][33][34] , such as high mechanical strength, excellent fracture toughness, good H 2 S resistance, reduction of the Bauschinger effect and superior fatigue behavior, than the polygonal ferrite -pearlite microstructure. The distribution of inclusions in the two steels was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in steel coil production facilities have enabled the possibility to manufacture spiral welded pipes with sufficient wall thickness and of adequate steel grade quality (strength and toughness properties) [2][3][4]. Based on the work of several research groups it can be concluded that in comparison to UOE-pipes, spiral pipes can perform equal or better when considering the following elements: cold field bending [5], buckling resistance [6], fracture arrest [7,8], ductile tearing [9], plastic collapse [10], bending [11], and burst fracture tests [12]. However, the evaluation of spiral pipe performance and its applicability in a tensile strain-based design context has received little attention [13].…”
Section: Introductionmentioning
confidence: 99%